Management strategies, silvopastoral practices and socioecological drivers in traditional livestock systems in tropical dry forests: An integrated analysis - Sánchez-Romero, Rosa; Balvanera, Patricia; Castillo, Alicia; Mora, Francisco; García-Barrios, Luis E.; González-Esquivel, Carlos E. (Forest ecology and management, 2021)
•An integrated socio-ecological analysis was applied to livestock management in forests.•Regional drivers (climate, native vegetation, markets) influence livestock management.•Local factors, such as resource access, determine management strategies.•Adaptive management involves knowledge, objectives, perceptions and preferences. Understanding traditional livestock management is essential in the design of more sustainable systems, given the forest loss associated to the growing demand for meat. In Latin America, where extensive livestock production is increasing, along with tropical dry forest (TDF) transformation, the role of small holders is critical for designing more sustainable management practices. This study is an integrated socioecological analysis of traditional livestock systems in a region with TDF in Mexico. The objectives were to: a) characterise the historical development and current state of livestock systems and silvopastoral practices, b) define the management strategies and their impacts on forests, and c) identify the regional and local socioecological drivers that influence decision-making processes in livestock and forest management. In-depth interviews were carried out to 32 cattle farmers and analysed using a qualitative-interpretative approach which included multivariate and narrative analyses. Three historical stages (colonization, promotion of livestock and forest conservation) had a strong impact in the development and current state of livestock systems. Access to natural and economic resources and proportion of plant cover (grassland/forest) were essential in defining four groups of management strategies. The main regional drivers favouring or restricting production include climate, native vegetation, markets and public policies; at the local scale, socioecological factors, such as water availability, native vegetation, economic assets, local knowledge and their interactions determine heterogeneity in management strategies, decision-making processes and their impacts on forests. Adaptive management of livestock and forests in a context of limited economic resources has allowed the conservation of forest areas and the use of silvopastoral practices with local tree species. The integrated socio-ecological approach and the use of mixed methods allowed a better understanding of drivers and their interrelationships, the local knowledge, objectives and perceptions of farmers in the decision-making processes regarding livestock and forest management. Perspectives of farmers on resource use can contribute to the design of more effective and inclusive policies for sustainable livestock systems in the dry tropics.